The effect of visual pollution resulting from change the residential buildings elevation in receiving the image - jassim, Shaymaa fadhel (Nahrain University College of Engineering Journal, 2011)
The research includes study the visual al pollution as a phenomenon spread in the large cities greatly, due to many factors as the fast technology development and misuse the structural planning in addition to wrong behaviors of environment's users, the matter which affect greatly in receiving the image at the recipient. Then the visual pollution result from many factors such as signification marks especially trade marks of all its types, colors, shapes and volumes as well misdistribution the street furniture and garbage containers and random the buildings frontages in respect of finishing materials, disarrangement gaps and bulges between blocks, and cheating the design and alteration it as to the residential buildings in form leads to non agreement with design, regarding to the importance of residential buildings in our life, will concentrate the research on studying the visual pollution which result from alteration of the residents to the image of residential buildings randomly. From review researches to be clear of existence a problem with regard to studying the visual pollution, and then finished it studying out of the role of signification marks especially trade marks and some of the street's furniture role; but it does not finish the study of visual pollution which result from change the residential buildings images, based on that, the aim of research it will be ( The effect of visual pollution resulting from the random change of the residential buildings images in receiving the image at recipient ). The problem of research will be (non obviousness the role of visual pollution which result from change of the residential buildings frontages in receiving the image at recipient). To solve the research's problem this matter will require the following: - First: Putting words describe the visual pollution and the role of recipient. Second: Doing a practical study includes choosing a residential assembler as a pattern to analysis it and choice a pattern of recipients to questionnaire them by using scale of variation of the indicative difference. The research supposes that changing frontages of the residential buildings randomly by residents which not agree with the design leads to visual pollution, and the excess by this matter leads the frontage to loss its archetype, the matter which result from it confusion and disturbance in relation to the recipient which leads to un realization the image clearly and then pollution the environment and not interaction the recipient with it.